The insect vector Cacopsylla picta vertically transmits the bacterium 'Candidatus Phytoplasma mali' to its progeny. (19th January 2017) - Mittelberger, C.; Obkircher, L.; Oettl, S.; Oppedisano, T.; Pedrazzoli, F.; Panassiti, B.; Kerschbamer, C.; Anfora, G.; Janik, K.
Abstract : The phloem‐sucking psyllid Cacopsylla picta plays an important role in transmitting the bacterium ' Candidatus Phytoplasma mali', the agent associated with apple proliferation disease. The psyllid can ingest ' Ca . Phytoplasma mali' from infected apple trees and spread the bacterium by subsequently feeding on uninfected trees. Until now, this has been the most important method of ' Ca . Phytoplasma mali' transmission. The aim of this study was to investigate whether infected C. picta are able to transmit ' Ca . Phytoplasma mali' directly to their progeny. This method of transmission would allow the bacteria to bypass a time‐consuming reproductive cycle in the host plant. Furthermore, this would cause a high number of infected F1 individuals in the vector population. To address this question, eggs, nymphs and adults derived from infected overwintering adults of C. picta were reared on non‐infected apple saplings and subsequently tested for the presence of ' Ca . Phytoplasma mali'. In this study it was shown for the first time that infected C. picta individuals transmit ' Ca . Phytoplasma mali' to their eggs, nymphs and F1 adults, thus providing the basis for a more detailed understanding of ' Ca . Phytoplasma mali' transmission by C. picta .